Expert consensus on prevention and control of COVID-19 in the neurological intensive care unit (first edition). Issue 3 (8th July 2020) - Wang, Furong; Liu, Jingyi; Zhang, Ping; Jiang, Wen; Zhang, Le; Zhang, Meng; Teng, Junfang; Wang, Jinquan; Xie, Xiaoqi; Cao, Jie; Li, Wei; Wu, Yongming; et al.
Abstract : During the COVID-19 epidemic, the treatment of critically ill patients has been increasingly difficult and challenging. During the epidemic, some patients with neurological diseases also have COVID-19, which could be misdiagnosed and cause silent transmission and nosocomial infection. Such risk is high in a neurological intensive care unit (NCU). Therefore, prevention and control of epidemic in critically ill patients is of utmost importance. The principle of NCU care should include comprehensive screening and risk assessment, weighing risk against benefits and reducing the risk of COVID-19 transmission while treating patients as promptly as possible.